2020
DOI: 10.1108/wjemsd-10-2019-0080
|View full text |Cite
|
Sign up to set email alerts
|

Mediation role of diversity climate on leadership and job satisfaction in the Ghanaian public sector

Abstract: PurposeThis study examines the mediation role of diversity climate in the relationship between transformational leadership, transactional leadership and job satisfaction from the two-factor perspectives of intrinsic and extrinsic job satisfactions among local government servants in Ghana.Design/methodology/approachThe study uses cross-sectional data from 322 employees in local government service of Ghana in the Greater Accra Region using purposive and stratified sampling methods. Bootstrapping method of mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 59 publications
3
27
0
3
Order By: Relevance
“…The result has identified that transactional leadership (TRL) has a positive but insignificant effect on workplace diversity. This result is in line with Mickson et al (2020) that an increase in TRL cannot increase diversity as the leaders might not be providing good benefits or incentives to raise the diversity. Besides, the TRL has been identified as an essential factor, but it can sometimes be insignificant as the employees might not be delighted with the advantages or worth of the task in which the employees are engaged (Blau, 1968).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The result has identified that transactional leadership (TRL) has a positive but insignificant effect on workplace diversity. This result is in line with Mickson et al (2020) that an increase in TRL cannot increase diversity as the leaders might not be providing good benefits or incentives to raise the diversity. Besides, the TRL has been identified as an essential factor, but it can sometimes be insignificant as the employees might not be delighted with the advantages or worth of the task in which the employees are engaged (Blau, 1968).…”
Section: Discussionsupporting
confidence: 83%
“…Like, "In my organization, people are flexible and adaptable when changes are necessary." Transformational leadership contains four items adapted from Mickson, Anlesinya, and Malcalm (2020). For example, "My leader provides vision and sense of mission, instills pride, gains respect and trust."…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selain itu kepemimpinan yang melayani juga berhubungan positif dengan kepuasan kerja (Aboramadan et al, 2020). Selain itu, dimensi dan gaya kepemimpinan transformational memberikan dampak positif terhadap kepuasan kerja individu dan tim, baik secara kepuasan kerja instrinsik dan ekstrinsik (Braun et al, 2013: Khan et al, 2020: Mickson et al, 2020: Top et al, 2015. Meski demikian, manajemen dengan partisipasi tidak selalu dikaitkan dengan gaya kepemimpinan, sehingga pemimpin organisasi harus tetap dilatih dan dibimbing untuk menemukan gaya kepemimpinan yang sesuai (Mosadeghrad dan Ferdosi, 2013: Song et al, 2020.…”
Section: Pendahuluanunclassified
“…Kompetensi komunikasi yang dimiliki oleh anggota orga-nisasi juga sebagai predictor kepuasan kerja (Madlock, 2017). Pembentukan persepsi dari semua interaksi yang dilakukan dan didukung dengan kualitas komunikasi juga dapat memberikan rasa puas kepada karyawan (Brohi et al, 2018 (Erben et al, 2019: Braun et al, 2013: Khan et al, 2020: Mickson et al, 2020: Top et al, 2015. Dengan demikian peran pemimpin sangat dibutuhkan dalam mengelola organiasi dan unsur-unsur yang mempengaruhi termasuk kepuasan kerja (Riana et al, 2020…”
Section: Hasil Goodness Of Fit Model Testunclassified